NEWCASTLE DISEASE MATERNAL ANTIBODIES DETECTION IN BROILERS - Permana, Ida Bagus Ketut Indra; Suardana, Ida Bagus Kade; Nindhia, Tjokorda Sari (Buletin Veteriner Udayana, 2022)
Nevertheless, it is often found that the after vaccination antibody titers is not as expected due to the existance of maternal antibodies. A passive maternal antibodies can inhibit formation of imunoglobulin and neutralize the antigen vaccines. According to that above mentioned explanation, this research aims to detect the maternal antibodies of Newcastle Disease in broilers to carefully identify when the chicken should be vaccinated. As the main object of study, 10 unvaccinated broilers would be included in this research. These samples would be grouped by 3 different times of collecting blood, namely at the age of 7 th , 14 th , and 21 st days. Blood sampling is subsequently carried out through branchialis vein that concludes 10 serum samples from each day. The respective samples will be serologically examined by conducting the haemaglutination (HA) and haemaglutination inhibition (HI) analysis to generate the antibody titers. All the data produced in this research will statistically processed by using descriptive statistical and regression tests on the SPSS software. The results showed a decrease in the maternal antibody titer of Newcastle Disease in broilers aged 7 days with a titer of 6.1 HI log 2, to 2.8 HI log 2 at 14 days of age, and 1.8 HI log 2 at 21 days of age. The Newcastle Disease vaccination program is most appropriate when the broiler is 10 days old because the maternal antibody titer is already at the positive threshold, namely 4 HI log 2.